NON-FINANCIAL FACTORS IN THE GOING-CONCERN OPINION - Junaidi, Junaidi; Hartono, Jogiyanto (Journal of Indonesian Economy and Business, 2010)
This paper describes the influence of tenure, auditor reputation, disclosure, and the size of the client company on a going concern opinion. Audit opinion issued by the auditoris expected by users of the quality of information, because as the basis for investment decisions. Going-concern audit opinion is an opinion issued by auditors to ascertainwhether the company can maintain its existence. Studies on the factors that affect the audit opinion have been carried out both overseas and in Indonesia. The factors used are vary and the results are not conclusive. This study uses 89 sample firms listed on the Indonesia Stock Exchange in 2003-2008. Logit regression analysis shows that the tenure, auditor reputation, disclosure has a significant on going-concern opinion while the client company size has no effect on going-concern opinion.Keywords: tenure, auditor reputation, disclosure, size, going-concern opinion